Antibiofilm Activity of Silver Nanoparticles Synthesized from Seed Extract of Garcinia Kola - Patricia, Okonofua Eghe; Nkene, Istifanus Haruna; David, Bando Christopher; Hannah, Nuhu Tubasen; Ngozi, Odii Josephine; Rebecca, Ayodele; Odii, Umahi Onu (Asian Journal of Science, Technology, Engineering, and Art, 2024)
Silver nanoparticles from plant extracts are novel compounds with potential antimicrobial properties. Studies on antibiofilm activity of Ag-NPs synthesized from seed extracts of Garcinnia kola (G. kola) were carried out. Garcinnia kola seed were obtained from Keffi market, Nigeria. Green synthesis of Ag-NPs from the seed was carried using 2.0mm silver-nitrate by use of standard method. The Ag-NPs synthesized from the seed were characterized using former transmission infrared (FITR) spectroscopy and scanning election microscope. The antimicrobial activity of the Ag-NPs against Klebsiella pneumonia (Kp) isolates were carried out using agar dilution method. The biofilm formation by the isolates as well as the inhibition and dissolution by Ag-NPs were eval__uated using microplate method. The functional groups detected in the Ag-NPs were N-H, C-O, N-O, and CΞC with peaks 906.5cm-1,1282.2cm-2, 13344cm-1, 1550.6cm-1 and 217.1cm-1 respectively. The size of the particles ranges from 179-296nm. The minimum inhibiting concentration (MICs) of the particles and meropenem against the isolates were 250µg/l and 4.0µg/l. The functional inhibiting concentrates of the particles were 1.0. The optical clarity of biofilm formed by the isolates was 2.073 and 2.049. the percentage biofilm inhibiting effects of the particles was highest apart. KpC (K. Pneumoniae ATCC BAA 1075) with percentage inhibit ranges from 27.28-21.67% at 80-12.5% of the MICs. The percentage inhibiting effect of Ag-NPs in with meropenem was highest at MICs but low in MIC 12.5 with percentage inhibition 28.26% and 27.18%. The Ag-NPs alone and antibacterial activity and biofilm inhibiting effect while Ag-NPs in with meropenem had effect but against isolate but with potential antibiofilm activity.